Fine Euhedral Banding in Zircon - Metamorphic Enhacement of Igneous Structure - HARTMANN, LÉO; VASCONCELLOS, MARCOS; LEITE, JAYME; McNAUGHTON, NEAL (Pesquisas em Geociências, 1999)
Fine euhedral banding of zircon is usually considered to be associated with magmatic crystallization processes. This is commonly true, but it can also be generated by solid-state replacement along bands in previously more homogeneous crystals. Zircons from the Neoproterozoic Cambaí Complex in southernmost Brazil show abundant evidence to support solid-state replacement. Investigations of more than 135 zircon crystals by Electron Probe Microanalysis and Electron Backscattering techniques show that the solid-state replacement process begins along fractures and expands to broad irregular patches, even forming younger nucleii in some crystals. The replacement continues along crystallographically-controlled bands, enhancing and resembling fine oscillatory igneous zoning. Microprobe analyses indicate that modified zones are enriched in Y, U and T in most BSE-bright bands, but in Hf in some others. The lighter (in BSE) parts in the core are texturally younger than the more homogeneous rims. The mechanisms involved include infiltration along fractures and defect sites and fluid-aided volume diffusion in less defective portions.